Business Process Improvement Using Bpi Method in the Implementation of Communication Network Device to Support Online Bank Branch Office and ATMs - Yuliawan Cahya Pamungkas; Ahmad Nurul Fajar (Universitas Bina Darma, 2022)
Business Process Improvement or BPI is a systematic framework built to assist organizations in making significant progress in the implementation of their business processes. BPI provides a system that will assist in the streamlining of business processes, by guaranteeing that internal and external customers of the organization will get better output than before, the purpose of this research is to provide business process improvement solutions with the BPI methodology in the implementation of the network device to support online ATM dan branch office. PT bank ABC is one of the biggest state-owned banks in Indonesia, which was established on December 16, 1895, in Purwokerto, Central Java. Currently has more than 20,000 office locations throughout Indonesia, where all these offices are online using Fiber Optic, MPLS, and VSAT technology, currently the business flow of the implementation process has not been optimal and is monitored manually with a long bureaucracy. An analysis of the activities in each business process is carried out where each of these activities has different characteristics, where we find 7 activities have value as real value-added (RVA) 6 activities that have value as business value-added (BVA), and 20 activities that have value as non-value added (NVA). Using streamlining tools provided by BPI we can streamline the existing business processes where from the results of streaming on the old business process we get 20 activities that have value as NVA can be streamlined using the Bureaucracy Elimination tool and 13 activities that have value as BVA and RVA can be streamed using the Upgrading tool. The results of the analysis are obtained by comparing the current business process and what is proposed from this research. After process improvement, The results of the simulation using bizagi software show that the processing time required to run the process is shorter in the recommended business process compared to the existing business process, where the average time required before is 10 Days 3 Hours 38 Minutes 45 Seconds with 33 activities involved and after we streamline it with Bureaucracy Elimination tool and Upgrading tool, we found the new average time is 3 Days 2 Hours 42 Mins 30 seconds and the new business process only have 14 activities. Based on the evaluation and simulation results that we have done Further research can use the evaluation results as a reference in the preparation of analysis and development of software applications and further research can develop an analysis that uses cost details that are not available in this research.